2005
DOI: 10.2987/8756-971x(2006)21[344:vcftso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation-Derived Cues for the Selection of Oviposition Substrates by Anopheles Albimanus Under Laboratory Conditions

Abstract: Oviposition response of gravid Anopheles albimanus Wiedemman (Diptera: Culicidae) females to water containing Brachiaria mutica, Cynodon dactylon, Jouvea straminea, Fimbristylis spadicea, and Ceratophyllum demersum was investigated. Gravid An. albimanus females deposited similar egg numbers in cups containing natural plants in water from natural breeding sites and in cups containing natural plants in distilled water. Gravid mosquitoes deposited significantly more eggs in cups containing natural plants in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…While gravid anopheline mosquitoes display preferences for volatiles associated with living plants41 and microbes associated with their larval habitats1920, culicines prefer those associated with the microbial fermentation of plant tissues2542. Here, we have identified a long-range plant odour-based attractant blend of readily available and affordable organic compounds for gravid malaria mosquitoes, providing the integrated vector management community with new perspectives for developing a tool that targets gravid anophelines regardless of feeding and resting preferences.…”
Section: Discussionmentioning
confidence: 98%
“…While gravid anopheline mosquitoes display preferences for volatiles associated with living plants41 and microbes associated with their larval habitats1920, culicines prefer those associated with the microbial fermentation of plant tissues2542. Here, we have identified a long-range plant odour-based attractant blend of readily available and affordable organic compounds for gravid malaria mosquitoes, providing the integrated vector management community with new perspectives for developing a tool that targets gravid anophelines regardless of feeding and resting preferences.…”
Section: Discussionmentioning
confidence: 98%
“…pipiens pallens females were attracted to terpenoids such as (E)-β-ocimene, α-pinene, β-pinene, D-limonene and linalool (Yu et al 2015). Torres-Estrada et al (2005) identified several compounds from plant extracts, including longifolene and caryophyllene, as attractants for oviposition of An. albimanus.…”
Section: Discussionmentioning
confidence: 99%
“…and Utricularia sp. (Torres-Estrada et al 2005), and with Dalbergia , Costus , Cyperus , Wedelia , Desmodium , Orizam , Abutilon , Calathea and Utricularia (Solarte et al 1994, Torres-Estrada et al 2005). It has likewise been observed in urban areas (Olano et al 1997) and areas disturbed by human activity.…”
Section: Primary Malaria Vector Speciesmentioning
confidence: 99%